Toward the Development of a New Libyan Local Chicken Breed - Ahmad, Hasan Moftah Ahmed; Yousaf, Muhammad Rizwan; Ahmed, Bilal; Kurnianto, Edy; Setiaji, Asep; Mustofa, Fatmawati; Lestari, Dela Ayu; Sutopo, Sutopo (ANIMAL PRODUCTION, 2025)
This study aims to describe the Libyan chicken breed and its origin, and to evaluate its potential for the development of a new Libyan local chicken breed with high genetic quality and productivity. A qualitative research design has been implemented to carry out this research with a descriptive-analytical approach. Data collection was done by reviewing scholarly literature from scientific journals, academic books, and credible online databases. This research analyzed previous studies to determine patterns that outline the genetic potentials, challenges, and opportunities in breeding programs for enhancing the productivity and resilience of Libyan local chickens. The results showed that the indigenous chicken varieties of Libya, such as Gallus gallus, Baladi or El-Balad, and Hypeco, are essential to the nation's agricultural and culinary traditions. These varieties are hardy and ideal for rural and semi-urban locations with limited access to contemporary farming infrastructure. This study's findings highlight Hypeco's potential as a top contender for the creation of a new breed of locally grown chickens in Libya with superior genetic quality and productivity. In the face of issues with food security, their resilience to intense heat, limited feed supply, and limited water supplies makes them priceless assets. A lack of effective farming methods, contemporary breeding procedures, and the required infrastructure limits these local hens' production and economic viability. These local hens' production and economic viability are limited by a lack of effective farming methods, contemporary breeding procedures, and the required infrastructure. Building infrastructure to assist the regional poultry business should also be a priority. This entails expanding access to veterinary care, storage facilities, water, and high-quality feed.